2021
DOI: 10.1097/cm9.0000000000001762
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of metachronous gastric neoplasms after curative endoscopic submucosal dissection for early gastric neoplasms

Abstract: Background: With the wide application of endoscopic submucosal dissection (ESD) for early gastric neoplasms, metachronous gastric neoplasms (MGN) have gradually become a concern. This study aimed to analyze the characteristics of MGN and evaluate the treatment and follow-up outcomes of MGN patients. Methods: A total of 814 patients were retrospectively enrolled. All these patients were treated by ESD for early gastric cancer or gastric dysplasia between November 2006 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 37 publications
(72 reference statements)
1
5
0
Order By: Relevance
“…Previous studies showed that up to 96% of MGL were amenable to ER [10,14,[17][18][19][20] or, less frequently, to surgical resection [10,14,[17][18][19][20]. This supports the recommendation of tight (annual) and long-term endoscopic surveillance to ensure early detection of MGL [3-5, 14, 16, 19, 21].…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Previous studies showed that up to 96% of MGL were amenable to ER [10,14,[17][18][19][20] or, less frequently, to surgical resection [10,14,[17][18][19][20]. This supports the recommendation of tight (annual) and long-term endoscopic surveillance to ensure early detection of MGL [3-5, 14, 16, 19, 21].…”
Section: Introductionsupporting
confidence: 58%
“…The median time to metachronous lesions of 30 months outlines the importance of endoscopic surveillance in the first 3 years after ESD. The current guidelines do not define the extent of surveillance, and the longest intervals described in previous studies for MGL detection were 8.3 and 9.7 years [15,17]. Given the high cumulative rate of MGL, endoscopic surveillance is probably of benefit beyond 5 years after ESD [5,8,19,20], but a one-size-fits-all approach can be challenged.…”
Section: Original Articlementioning
confidence: 96%
See 1 more Smart Citation
“…However, this is too lenient for evaluating lesions of HpC-EGC patients with an average diameter <2 cm. In this case, we adopted "precise delineation" in this 2 Precise delineation: when D min of a lesion was >5 mm, it would be absolutely ensured with negative horizontal margins and regarded as safe. 3 D min : D is referred to the distance between marking dots and the PDL (when the PDL was inside marking dots, D was recorded as a positive value; otherwise, it was recorded as 0 mm), and D min was the shortest one of all marking dots in all slices of one en bloc-resected lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Early gastric cancer (EGC) is defined as gastric adenocarcinoma limited to the mucosa or submucosa of the stomach, regardless of lymph node status [1]. Endoscopic submucosal dissection (ESD) has been proven to perform curative resection for EGC in cases with a low risk of lymph node metastasis, achieving equivalent effectiveness with structural integrity compared to surgery [2][3][4][5]. In this process, complete resection is essential for the operation's curability, including negative horizontal resection margins [6].…”
Section: Introductionmentioning
confidence: 99%